Identification of the Visceral Pain Pathway Activated by Noxious Colorectal Distension in Mice - Kyloh, Melinda; Nicholas, Sarah; Zagorodnyuk, Vladimir P.; Brookes, Simon J. H.; Spencer, Nick J. (Frontiers in Neuroscience, 2011)
In patients with irritable bowel syndrome (IBS), visceral pain is evoked more readily following distension of the colorectum. However, the identity of extrinsic afferent nerve pathway that detects and transmits visceral pain from the colorectum to the spinal cord is unclear. In this study, we identified which extrinsic nerve pathway(s) underlies nociception from the colorectum to the spinal cord of rodents. Electromyogram (EMG) recordings were made from the transverse oblique abdominal muscles in anesthetized wild type (C57BL/6) mice and acute noxious intraluminal distension (100-120 mmHg) applied to the terminal 15mm of rectum to activate visceromotor responses (VMRs). Cutting the lumbar colonic nerves in vivo had no detectable effect on the VMRs evoked by colorectal distension. Lesioning right or left hypogastric nerves also failed to reduce VMRs. However, lesioning left and right branches of the rectal nerves completely abolished the VMRs, regardless of whether the lumbar colonic or hypogastric nerves were severed. Electrical stimulation applied to either the lumbar colonic or hypogastric nerves in vivo, failed to elicit a VMR. In contrast, electrical stimulation (2-5Hz, 0.4ms, 60V) applied to the rectum reliably elicited VMRs, which were abolished by selective lesioning of the rectal nerves. DiI retrograde labelling from the colorectum labelled sensory neurons only in dorsal root ganglia (DRG) of the lumbosacral region of the spinal cord. In contrast, injection of DiI into the mid to proximal colon labelled sensory neurons in DRG primarily of the lower thoracic level (T8-L4) of the spinal cord. The visceral pain pathway activated by acute noxious distension of the terminal 15 mm of mouse rectum is transmitted predominantly, if not solely, through rectal/pelvic afferent nerve fibres to the spinal cord. The sensory neurons of this spinal afferent pathway lie in the lumbosacral region of the spinal cord, primarily at the level of S2 and S3.